Efficacy and pharmacoeconomic advantages of Fufang Huangbai Fluid hydropathic compress in diabetic foot infections: a comparative clinical study with antimicrobial calcium alginate wound dressing - Yang, Guangyao; Wang, Gang; Li, Zhenghong; Deng, Lijuan; Wang, Ning; Wang, Xuewan; Zhou, Tong; Zhang, Jingming; Lei, Yin; Wang, Tao; Wang, Yue; Shao, Hanying; et al. (Frontiers in Pharmacology, 2024)
Objective To compare the intervention effects and pharmacoeconomic advantages of Fufang Huangbai Fluid (FFHB) hydropathic compress versus Antimicrobial Calcium Alginate Wound Dressing (ACAWD) in the treatment of diabetic foot infections（DFI）. Methods Patients with DF who were hospitalized in the peripheral vascular Department of Dongzhimen Hospital of Beijing University of Chinese Medicine from December 2020 to February 2022 and met the inclusion and excluding criteria were allocated into the experimental group and control group through minimization randomization. The experimental group was treated with FFHB hydropathic compress for two weeks, while the control group was treated with ACAWD for the same duration. The wound healing of both groups was monitored for one month post-discharge. Clinical data from all eligible patients were collected, and differences in various indices between cohorts were analyzed. Results 22 in the experimental group (including two fell off) and 20 in the control group. After the treatment, the negative rate of wound culture in the experimental group was 30% and that in the control group was 10%, There was no significant difference in the negative rate of wound culture and change trend of minimum inhibitory concentration (MIC) value of drug sensitivity (P>0.05).The infection control rate of the experimental group was 60%, and that of the control group was 25%. The difference between the two groups was statistically significant (χ2=5.013，p=0.025).The median wound healing rate of the experimental group was 34.4% and that of the control group was 33.3%. There was no significant difference between the two groups (P>0.05). During the follow-up one month later, the wound healing rate in the experimental group was higher, and the difference was statistically significant (p=0.047). Pharmacoeconomic evaluations indicated that the experimental group had greater cost-effectiveness compared to the control group. Conclusions In the preliminary study, FFHB demonstrated comparable pathogenic and clinical efficacy to ACAWD in the treatment of mild DF infection, and exhibited superior pharmacoeconomic advantages. With the aid of infection control, the wound healing rate in the FFHB group showed notable improvement. Nevertheless, due to the limited sample size, larger-scale studies are warranted to further validate these findings.